Mineralogy of Noble Metals and "Invisible" Speciations of These Elements in Natural Systems, Volume II - Palyanova, Galina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue book includes one review and eleven research articles. This review presents the results of studies on the noble metal forms in pyrite, arsenopyrite, chalcopyrite, sphalerite, and greenockite and summarizes the distribution and speciations of noble metals in base metal sulfides of Au and Au-bearing deposits of the Urals (Russia). Nine research articles are devoted to studying gold mineralization at different types of gold deposits and the characterization of the conditions of its formation. The typomorphism of placer gold and its distribution mechanisms in the east of the Siberian Platform were studied, and the diagnostic method and morphogenetic criteria for identifying the genesis of placers and different sources in the platform areas were proposed in other research articles. One research article presents an experimental study of Pt solubility in a CO-CO2-rich fluid. These studies contribute to a better understanding of the behavior of Au, Ag, and other noble metals; their forms in ore-forming systems; and the genesis of ore deposits. I sincerely appreciate the efforts and contributions of the Authors and Reviewers and would also like to express gratitude to the Editor-in-Chief, other Editors, and Assistant Editors of Minerals for their help.